Research Brief: Self-Reports of a Constellation of Persistent Antiandrogenic, Estrogenic, Physical, and Psychological Effects of Finasteride Usage Among Men - Walf, Alicia A. (Am J Mens Health, 2018)
Our research objective is to understand more, through subjective, self-reports on discussion boards/forums, persons’ experiences associated with the use of drugs that alter androgen metabolism, such as finasteride. Finasteride is an orally active, specific inhibitor of 5α-reductase, which is localized to many androgen-dependent tissues. Finasteride inhibits the conversion of testosterone (T) to dihydrotestosterone (DHT), and is commonly used to treat benign prostatic hypertrophy (BPH) and male pattern baldness (MPB), both disorders associated with elevated DHT levels and 5α-reductase activity in the prostate and hair follicles, respectively. It is now acknowledged that long-term use and discontinuation of finasteride has adverse effects (AEs); however, these claims have not been well documented. In this study, discussion board posts (forums) were analyzed as self-reports of what finasteride users indicate is problematic for them. Reports were categorized by the age of subjects as well as the types of AEs described: antiandrogenic, estrogenic, central, and nonspecific/severe. A total of 244 cases were recorded and analyzed on the discussion forum on propeciahelp.com. Among these, 74 (32%) cases reported antiandrogenic affects, 43 (19%) reported estrogenic effects, 70 (30%) reported central effects, 11 (5%) reported nonspecific/severe AEs, and 31 (14%) reported AEs in all categories. The categorization of AEs may prompt further investigation into the pathophysiology of post-finasteride syndrome (PFS). Also, subjective reports may engender greater understanding of the perceived lasting AEs of finasteride.